THE ROLES OF CONSUMERâS KNOWLEDGE AND EMOTION IN ECOLOGICAL ISSUES: An Empirical Study on Green Consumer Behavior - Junaedi, M. F. Shellyana (Gadjah Mada International Journal of Business, 2007)
This study examines the causal effect of existing relationship amongst green purchasing, which are attitudinal and behavioral approaches, consumer values, ecological affect, ecological knowledge, and green purchase intention. The survey result provides a reasonable support for the validity of the proposed model. Specifically, the finding from structural equation model confirms the influence of consumer values orientation, ecological affect, and ecological knowledge on their attitudes towards green purchase intention. The implication of this research is relevant to Indonesian government and green marketers to fine-tune their environmental programs.